قياس موافقة معايير مقترحة للرخصة المهنية لمعلم مادة التربية الإسلامية من وجهة نظر الخبراء التربويين - المطيري، مها هذال (جامعة كفر الشيخ - كلية التربية, 2023)
هدفت الدراسة إلى التعرف على قياس موافقة معايير مقترحة للرخصة المهنية لمعلم مادة التربية الإسلامية في المرحلة الابتدائية بدولة الكويت من وجهة نظر الخبراء التربويين، وأثر متغيرات (النوع، سنوات الخبرة) في ذلك، ولتحقيق أهداف الدراسة تم استخدام المنهج الوصفي، وتم جمع البيانات من خلال استبانة تضمنت (۳۰) عبارة موزعة على أربعة جوانب، وهي: ١- معايير مهارات معرفية متخصصة، ٢- معايير مهارات تدريسية 3-معايير مهارات الإدارة الصفية، ٤- معايير مهارات التفكير العليا، وقد طبقت على عينة تكونت من (٥٢) موجها وموجهة للتربية الإسلامية، وتوصلت النتائج إلى أن معايير مقترحة للرخصة المهنية لمعلم مادة التربية الإسلامية في المرحلة الابتدائية ككل لدى أفراد عينة الدراسة جاءت بدرجة كبيرة، وجاء في الترتيب الأول معايير مهارات معرفية متخصصة، يليها معايير مهارات تدريسية، ثم معايير مهارات الإدارة الصفية، وأخيرا معايير مهارات التفكير العليا. وأشارت النتائج إلى وجود فروق دالة إحصائيا بين متوسطات أفراد عينة الدراسة حول معايير مهارات الإدارة الصفية، ومعايير مهارات معرفية متخصصة وفقا لمتغير النوع بينما لا توجد فروق حول باقي المعايير، ولا توجد فروق حول الدرجة الكلية وفقا لمتغير سنوات الخبرة، وتوصي الدراسة بأهمية اعتماد معايير للترخيص المهني للمعلم في دولة الكويت بما يضمن تحقق معلمين أكفاء للمرحلة الابتدائية. The study aimed to identify the measurement of the approval of proposed standards for the professional license for the teacher of Islamic education at the primary stage in the State of Kuwait from the point of view of educational experts, And the effect of variables (type, years of experience) in that To achieve the objectives of the study, the descriptive approach was used, and the data was collected through a questionnaire that included (30) phrases distributed on four aspects, namely: 1- Specialized cognitive skills standards, 2- Teaching skills standards, 3- Classroom management skills standards, 4- Higher thinking skills standards, It was applied to a sample consisting of (52) directed to Islamic education, The results found that the proposed standards for the professional license for the Islamic education teacher at the primary stage as a whole among the members of the study sample came to a large degree, and came in the first place the standards of specialized cognitive skills, followed by the standards of teaching skills, then the standards of classroom management skills and finally the standards of higher thinking skills, The results indicated that there were statistically significant differences between the averages of the study sample members on the criteria of of classroom management skills& the criteria of specialized cognitive skills according to the gender variable, while there were no differences about the rest of the criteria, While there are no differences about the total degree according to the variable of years of experience, the study recommends the importance of adopting standards for professional licensing of teachers in the State of Kuwait to ensure the achievement of qualified teachers for the primary stage.
Keywords: الرخصة المهنية -- معلمو التربية الإسلامية -- المرحلة الابتدائية -- الكويت